DEVELOPMENT OF HISTORICAL MEMORY IN PRIVATE SCHOOL STUDENTS DURING THE UKRAINIAN LANGUAGE LESSONS - Nakonechna, Larysa; Kilichenko, Oksana (Mountain School of Ukrainian Carpaty, 2022)
The article is devoted to the topical issue of today - the formation of historical memory in primary school students. Historical memory is an important component of the strategy of national and cultural policy of the state, the system of national and patriotic education of children and youth in different levels ща educational institutions, as well as a factor in the unification of society and national self-identification. The purpose of the article is to analyze and describe effective ways of forming the historical memory of primary school children in the process of learning the Ukrainian language. To achieve this goal, the following research methods were used: analysis and synthesis, abstraction, generalization, and questionnaires, which allowed them to analyze the pedagogical conditions of historical memory of primary school students in Ukrainian language lessons and identify the main directions of this process. Based on numerous studies by scholars, the authors clarified the essence of the concept of "historical memory" in connection with other concepts of patriotic education and considered its significance for society as a guardian of the nation and a factor in national self-identification. They focused on those normative educational documents that define the essence and tasks of the process of forming the historical memory of citizens in Ukraine. External factors that affect the historical memory of the individual and which, of course, should be taken into account by teachers in working on the formation of historical memory of students are considered in detail. The authors considered in detail the ways of forming the historical memory of primary school students in Ukrainian language lessons and gave recommendations on the content of the relevant didactic material. They found that Ukrainian language lessons in primary school are a good basis for the formation of patriotic feelings and historical memory of younger students, to awaken students' deep connection with previous generations of their people, their cultural and historical achievements, their involvement in the great, strong, ancient people, a sense of pride for their homeland. Keywords: historical memory; patriotic education; Elementary School; Ukrainian language lesson.